Beispiel Nr: 17
$ \text{Gegeben: } \text{Nullstellen: } x_1\qquad x_2 \\ \text{Formefaktor: } a \\ \text{Gesucht: faktorisierte Form } y=a(x-x_1)(x-x_2) \\ \text{Allgemeine Form }y=ax^2+bx+c \\ \\ \text{Nullstellen - Faktorisierte Form}\\ \textbf{Gegeben:} \\ P(\frac{1}{3}/0)\qquad Q(-1/0) \\\\ \\ \textbf{Rechnung:} \\ P(\frac{1}{3}/0)\qquad Q(-1/0) \qquad a=1 \\ \text{Formfaktor a und Nullstellen in die faktorisierte Form einsetzen}\\ y=a(x-x_1)(x-x_2)\\ y=1(x-\frac{1}{3})(x+1)\\ y=1(x^2- x \cdot \left(-1\right) -\frac{1}{3}\cdot x +\frac{1}{3}\cdot \left(-1\right) )\\ y=1(x^2 +\frac{2}{3} x-\frac{1}{3}) \\ y= x^2-\frac{2}{3}x-\frac{1}{3} $